Organic passion fruit juice processed by microfiltration - Silva, Thadia Turon; Modesta, Regina Célia Della; Penha, Edmar das Mercês; Matta, Virgínia Martins da; Cabral, Lourdes Maria Corrêa (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to evaluate the use of microfiltration to obtain clarified organic passion fruit juice and analyse its sensory acceptability. Passion fruit was cultivated under organic system in Rio de Janeiro State. The juice was submitted to an enzymatic treatment before microfiltration, in order to decrease its viscosity and pulp content, and to improve permeate flux. Microfiltration had been accomplished with a tubular 0.3 µm pore size membrane with 0.05 m2 of filtration area. The process promoted complete removal of the suspended pulp in permeated juice, which resulted in a limpid and clarified juice. Concerning the sensorial analysis, passion fruit refreshment obtained from clarified juice was approved by 75% of the consumers. The microfiltered passion fruit juice was conserved in plastic package for 28 days under refrigeration temperature (7ºC). Results confirm the efficiency of microfiltration as an alternative method for conservation of passion fruit juice, and point out the importance of this technology for the processing of organic juices.